Inflammation in a ferroptotic environment - Wickert, Anja; Schwantes, Anna; Fuhrmann, Dominik C.; Brüne, Bernhard (Frontiers in Pharmacology, 2024)
Ferroptosis is an iron-dependent form of cell death, which finally culminates in lipid peroxidation and membrane damage. During the past decade, the interest in ferroptosis increased substantially and various regulatory components were discovered. The role of ferroptosis during inflammation and its impact on different immune cell populations is still under debate. Activation of inflammatory pathways such as nuclear factor kappa-light-chainenhancer of activated B cells (NF-κB) and hypoxia inducible factors (HIFs) are known to alter the ability of cells to undergo ferroptosis and are closely connected to iron metabolism. During inflammation, iron regulatory systems fundamentally change and cells such as macrophages and neutrophils adapt their metabolism towards iron sequestering phenotypes. In this review, we discuss how ferroptosis alters inflammatory pathways and how iron metabolism under inflammatory conditions affects immune cell ferroptosis.